PENGARUH SENAM RHYTMIC AUDITORY STIMULATION (RAS) DENGAN KEMAMPUAN BERJALAN LANSIA DI DESA KOHOD KABUPATEN TANGERANG (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2020)
Objective : The effect of the Rhytmic Auditory Stimulation (RAS) exercise on the walking ability in the elderly in the village of Kohod, Tangerang Regency. Method : This study was a quasi-controlled randomized experimental by collecting pre and post group 1 and group 2 TUG values, and collecting TUG values in group 1 compared to group 2 control. The study subjects consisted of 22 elderly (aged: 65.40 ± 5.76 years) divided into group 1 RAS gymnastics (n = 11) and control group 2 (n = 11). Data were analyzed using paired sample t-test and independent t-test to test the effect of  the RAS exercise on walking ability in the elderly. Results : paired sample t-test pre (13.20 ± 3.78) and post (9.87 ± 1.50) group 1 p = 0.01 (p <0.05) there were differences in walking ability, independent samples t -test post group 1 and group 2 p = 0.009 (p <0.05) there is a difference in the walking ability. Conclusion: RAS exercise can improve walking ability in the elderly and there are differences in the walking ability of RAS exercise compared with controls in the elderly.